A low computational complexity bandwidth extension method for mobile audio coding. (May 2017) - Hang, Bo; Kang, Changqing; Wang, Yi
Abstract: Mobile devices always demand low computational complexity because computing resources, such as processor and battery, in mobile are always limited. The bandwidth extension (BWE) algorithm in mobile audio codec standard of China was proposed to improve audio quality in mobile communication. But the computational complexity of the algorithm is too high to implement in mobile devices. By analyzing the BWE algorithm, we discover that the main reason of high computational complexity is the frequently usage of time-frequency transformation. Then a low computational complexity scheme is proposed, which include algorithm optimization and code optimization. The experiment results show that computation time consumption ratio of BWE module in encoder and decoder are decreased by 4.5 and 14.3 percentage points respectively, without reducing the overall audio codec subjective quality, which is be conductive to the algorithm implement in mobile audio field.